A consciência e sua formação no Vaticano II: Bernhard Häring, Optatam Totius e suas consequências no processo de discernimento na formação presbiteral - Sousa, Aloisio de Melo (2024)
This research aims to analyze the formation of conscience in the Second Vatican Council, in light of Bernhard Häring's theology, particularly regarding his approach to conscience. It also seeks to identify in the decree Optatam Totius his influence and contribution to the perspective of priestly formation. The renewal of the theological-moral method leads to a reflection on conscience towards new perspectives, already indicated by the renewal movement emerging in the 20th century, with Häring as a prominent figure, especially following his moral theology manual The Law of Christ, published a decade before Vatican II. Since the Council of Trent, there had been no such renewal in Catholic morals. As a sucessor of the casuistic method, the German theologian was influenced by the School of Tübingen, contributing to new perspectives of Catholic morality, which would be reflected in the discussions of Vatican II. Gaudium et Spes n. 16 emerges as the new definition of conscience, valuing aspects of freedom and human dignity, and presenting the realistic and personalista mode of the Council. Optatam Totius n. 16 calls for greater attention to the study of moral theology within the formative process and proposes a Christocentrism, in the light of Sacred Scripture, to fill this gap in priestly formation. The post-conciliar period is marked by attempts to implement its teachings; Häring writes the continuation of his theology manual, Free and Faithful in Christ, reaffirming the value of a free and responsible conscience. Discernment appears fundamental for a mature vocation, and Häring's theology provides aspects that help achieve such maturity. Current and future perspectives for priestly formation point to the formation of conscience as a safer path, towards a new formative culture aimed at mature discernment as a place of transformation